2009
DOI: 10.1103/physrevc.79.044916
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hydrodynamic expansion in relativistic heavy-ion collisions

Abstract: Hydrodynamic expansion of the hot fireball created in relativistic Au-Au collisions at √ s = 200GeV in 3 + 1-dimensions is studied. We obtain a simultaneous, satisfactory description of the transverse momentum spectra, elliptic flow and pion correlation radii for different collision centralities and different rapidities. Early initial time of the evolution is required to reproduce the interferometry data, which provides a strong indication of the early onset of collectivity. We can also constraint the shape of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 92 publications
5
85
1
Order By: Relevance
“…Our findings are qualitatively supported by the work [28] (whose authors, like us, used the source variances method) where it was found that an increase in the Knudsen number (or, equivalently, η/s) resulted in a decrease in R 2 o . The purpose of the present work is not a realistic comparison with experimental data which, as done in [15,16], would require a simultaneous tuning of several additional parameters (see also Ref. [29]).…”
Section: A Mean Hbt Radii and Their Kt Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are qualitatively supported by the work [28] (whose authors, like us, used the source variances method) where it was found that an increase in the Knudsen number (or, equivalently, η/s) resulted in a decrease in R 2 o . The purpose of the present work is not a realistic comparison with experimental data which, as done in [15,16], would require a simultaneous tuning of several additional parameters (see also Ref. [29]).…”
Section: A Mean Hbt Radii and Their Kt Dependencementioning
confidence: 99%
“…Studies such as [15,16] have explored the sensitivity of the HBT radii to shear viscosity using constant (Tindependent) η/s and varying that constant. Different from our approach here, when changing η/s they also changed other hydrodynamic parameters to ensure that not only the normalization but also the slope of the p Tspectra was held fixed.…”
Section: A Mean Hbt Radii and Their Kt Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of the longitudinal profile (54) were fitted to reproduce the pseudorapidity distribution of charged particles with the results being ∆ς = 2.5 and σ ς = 1.4. The shift in rapidity is calculated according to the formula [52] …”
Section: −1mentioning
confidence: 99%
“…The results of the hadron-gas model at lower temperatures are combined with the lattice results at higher temperatures in the thermody-namically consistent way described in [9]. However, the most attractive feature of our EOS is the fact that it was successfully implemented in 2+1 [10] and 3+1 [11] hydrodynamic codes describing heavy-ion collisions. Thus, in our case the knowledge from heavy-ion physics is transferred directly to cosmology.…”
mentioning
confidence: 99%